The intracellular parasite Toxoplasma gondii depends on the synthesis of long‐chain and very long‐chain unsaturated fatty acids not supplied by the host cell. Issue 1 (23rd April 2015) - Ramakrishnan, Srinivasan; Docampo, Melissa D.; MacRae, James I.; Ralton, Julie E.; Rupasinghe, Thusitha; McConville, Malcolm J.; Striepen, Boris
Summary Apicomplexa are parasitic protozoa that cause important human diseases including malaria, cryptosporidiosis and toxoplasmosis. The replication of these parasites within their target host cell is dependent on both salvage as well as de novo synthesis of fatty acids. In Toxoplasma gondii, fatty acid synthesis via the apicoplast‐localized FASII is essential for pathogenesis, while the role of two other fatty acid biosynthetic complexes remains unclear. Here, we demonstrate that the ER‐localized fatty acid elongation (ELO) complexes are essential for parasite growth. Conditional knockdown of the nonredundant hydroxyacyl‐CoA dehydratase and enoyl‐CoA reductase enzymes in the ELO pathway severely repressed intracellular parasite growth. 13C‐glucose and 13C‐acetate labeling and comprehensive lipidomic analyses of these mutants showed a selective defect in synthesis of unsaturated long and very long‐chain fatty acids (LCFAs and VLCFAs) and depletion of phosphatidylinositol and phosphatidylethanolamine species containing unsaturated LCFAs and VLCFAs. This requirement for ELO pathway was bypassed by supplementing the media with specific fatty acids, indicating active but inefficient import of host fatty acids. Our experiments highlight a gap between the fatty acid needs of the parasite and availability of specific fatty acids in the host cell that the parasite has to close using a dedicated synthesis and modification pathway.